Utilization of Rice Husk ash and Bamboo Leaf for Increasing Si for Rice Production on Paddy Soil - Suryono Suryono; Suwarto Suwarto; Ima Farohi (JOURNAL OF TROPICAL SOILS, 2019)
Silicate is an important  nutrient element  for rice plants. Rice is a plant that absorbs Si in large quantities. The low Si content in paddy fields is caused by intensive rice cultivation practices. Ash husk rice and bamboo leaves are materials that have a high silicate content so that the addition of husk ash and bamboo leaves can  increase the availability of Si in nature. This research used Randomized Complete Block Design (RCBD), the factor that was tested were Factor I (source of Si : S1, S2) and Factor II (Dosage: D0, D1, D2, D3, D4). The results showed there is significant difference on the available Si, Si uptakeorganic matter, total number tiller, weight of 1000 grains. The application of Rice ask hush dose 10 Mg ha-1 (S1D4) can increase available Si, Uptake Si, Organic Matter, total number tiller and weight of 1000 grains than the appliacation of bamboo leaf.